Effects on NOx and SO2 Emissions during Co-Firing of Coal With Woody Biomass in Air Staging and Reburning - Nihad Hodžić; Sadjit Metović; Anes Kazagic (International Journal of Renewable Energy Development, 2018)
Co-firing coal with different types of biomass is increasingly being applied in thermal power plants in Europe. The main motive for the use of biomass as the second fuel in coal-fired power plants is the reduction of CO2 emissions, and related financial benefits in accordance with the relevant international regulations and agreements. Likewise, the application of primary measures in the combustion chamber, which also includes air staging and/or reburning, results in a significant reduction in emission of polluting components of flue gases, in particular NOx emissions. In addition to being efficient and their application to new and future thermoblocks is practically unavoidable, their application and existing conventional combustion chamber does not require significant constructional interventions and is therefore relatively inexpensive. In this work results of experimental research of co-firing coals from Middle Bosnian basin with waste woody biomass are presented. Previously formed fuel test matrix is subjected to pulverized combustion under various temperatures and various technical and technological conditions. First of all it refers to the different mass ratio of fuel components in the mixture, the overall coefficient of excess air and to the application of air staging and/or reburning. Analysis of the emissions of components of the flue gases are presented and discussed. The impact of fuel composition and process temperature on the values of the emissions of components of the flue gas is determined. Additionally, it is shown that other primary measures in the combustion chamber are resulting in more or less positive effects in terms of reducing emissions of certain components of the flue gases into the environment. Thus, for example, the emission of NOx of 989 mg/ measured in conventional combustion, with the simultaneous application of air staging and reburning is reduced to 782 mg/, or by about 21%. The effects of the primary measures applied in the combustion chamber are compared and quantified with regard to conventional combustion of coals from Middle Bosnian basin.Article History: Received: November 5th 2017; Revised: Januari 6th 2018; Accepted: February 1st 2018; Available onlineHow to Cite This Article: Hodžić, N., Kazagić, A., and Metović, S. (2018) Experimental Investigation of Co-Firing of Coal with Woody Biomass in Air Staging and Reburning. International Journal of Renewable Energy Development, 7(1), 1-6.https://doi.org/10.14710/ijred.7.1.1-6